DETERMINAN REALISASI PMDN DI INDONESIA: ESTIMASI PANEL DINAMIS - Sari, Vita Kartika; Rahman, Yozi Aulia (Pusat Penelitian, Badan Keahlian DPR RI, 2023)
Investment becomes an important variable to achieve economic growth, especially in a developing country such as Indonesia. Investment is a tool for economic growth and recovery through capital stimulus for the production process that will be impactful on increasing household consumption. Investment can contribute to job creation, poverty reduction, and living standard improvement. Enhancement of domestic investment is needed to improve the development. The main purpose of this study is to analyze the effects of gross regional domestic product (GRDP), government spending, and years of schooling on the realization of domestic investment in 33 provinces in Indonesia from 2016 to 2020. The realization of domestic investment in Indonesia showed a positive trend that described a good indicator of investment growth in provincial level. Data estimation employed with first difference panel generalized method of moments. From the test results, the GRDP parameter is significantly positive towards domestic investment. Years of schooling is proven to have negative impacts on the realization of domestic investment. GRDP(-1) and government spending are proven to be not significant. The instrument validity test employing the Sargan test shows that the research model is valid. Through the Arellano-Bond Serial Correlation test, it is known that there is no serial correlation so that the model has good consistency. Therefore, investment policy stability is necessary to encourage the productivity of the productive sectors at the provincial level. Synergy between the central government and provincial government is needed to allocate the realization of domestic investment efficiently for the potential sectors.Keywords: domestic investment, gross regional domestic product, GMM panelAbstrakInvestasi merupakan variabel penting untuk mencapai pertumbuhan ekonomi, khususnya di negara sedang berkembang seperti Indonesia. Investasi merupakan alat pertumbuhan dan pemulihan ekonomi melalui stimulus modal untuk proses produksi yang akan berimbas pada meningkatnya konsumsi rumah tangga. Investasi dapat berkontribusi dalam penciptaan lapangan kerja, pengurangan kemiskinan, dan peningkatan standar hidup. Pemberdayaan penanaman modal dalam negeri (PMDN) perlu digalakkan sebagai sumber pembangunan yang penting. Tujuan utama studi ini adalah menganalisis pengaruh produk domestik regional bruto (PDRB), pengeluaran pemerintah, dan lama sekolah terhadap realisasi PMDN pada 33 provinsi di Indonesia periode 2016-2020. Realisasi PMDN di Indonesia menunjukkan tren positif, hal ini sebagai indikator terjadinya pertumbuhan investasi yang baik di level provinsi. Estimasi data menggunakan first difference panel generalized method of moments. Berdasarkan hasil pengujian, variabel PDRB terbukti signifikan positif terhadap PMDN. Variabel lama sekolah terbukti berdampak negatif terhadap realisasi PMDN. Variabel PDRB(1) dan belanja pemerintah terbukti insignifikan. Pengujian validitas instrumen dengan uji Sargan menunjukkan model penelitian valid. Melalui uji Arellano-Bond Serial Correlation, diketahui tidak terdapat serial korelasi sehingga model memiliki konsistensi yang baik. Strategi kebijakan investasi diperlukan untuk mendorong produktivitas sektor produktif di level provinsi. Diperlukan sinergi pemerintah pusat dan pemerintah provinsi untuk dapat mengalokasikan PMDN secara efisien untuk sektor-sektor unggulan daerah.Kata kunci: PMDN, PDRB, panel GMM